PENINGKATAN KOMPETENSI GURU SDN 26 KOTA BENGKULU DALAM PEMBELAJARAN DIGITAL INTERAKTIF MENTIMETER - Rizza Armelvia Sari; Retno Wahyuningtyas; Permata Jali Dimasiosz (LPPM Universitas Abdurrab, 2026)
The development of digital technology requires teachers to integrate technology-based interactive learning into the teaching process. The Covid-19 pandemic has significantly transformed educational practices, particularly the shift from face-to-face learning to online learning. This transition has required teachers to adapt to various digital applications that were previously unfamiliar. Du ring its implementation, several challenges emerged, including low student engagement, boredom, and limited active participation in learning activities. These conditions pose challenges for teachers to create engaging and interactive learning environments. However, not all teachers possess sufficient knowledge and skills in selecting and utilizing appropriate digital learning media. Based on these issues, this community service activity was conducted through a training program aimed at improving elementary school teachers’ understanding and competence in designing interactive digital learning using the Mentimeter platform, while also introducing the concept of Active Learning Strategies (ALS) in the digital era. The implementation methods included training sessions, guided practice, and evaluation. The activity was attended by 11 teachers of SDN 26 Kota Bengkulu and was conducted on November 21, 2025. The results indicate an improvement in teachers’ understanding of ALS concepts and their competence in using Mentimeter, as reflected in questionnaire results where the majority of participants gave responses in the good and very good 91% categories. These findings demonstrate that the training materials were relevant and effectively supported the development of teachers’ competencies in the teaching and learning process.